Retrospective study: Causes of Strigiformes admission at Parque Zoológico y Jardín Botánico Nacional Simón Bolívar, San José, Costa Rica during 1995-2015 (Ciencias Veterinarias, 2019)
Raptor populations, including the order Strigiformes, have declined in number and are threatened or endangered, not only by habitat destruction, but also by human activities. The objectives of present study were to describe the main causes of entry for the species of the Order Strigiformes in the Simón Bolívar National Zoological Park and Botanical Garden, as well as to summarize the primary clinical diagnoses, localities of origin and species entered, using the information generated in the records of admission during a period of 20 years (1995-2015). The following data were used from the entry sheets: date of entry, species, locality, and cause: (1) trauma, (2) orphans, (3) intoxication, (4) electrocution, (5) unknown causes. And the category of trauma was classified according to the type of injury: (1) fracture in extremities (anterior or posterior), (2) Brain head trauma (TCE), (3) Skin wounds. There were 352 individuals of nine species of Strigiformes, being the Neotropical owl (Megascops choliba) the most abundant species with 141 individuals (40.05%). The highest percentage of individuals came from the province of San José (80.91%, n=285). The trend of admissions per year was generally relatively homogeneous in a range of 10 to 20 individuals, except for 1999 (n=35) and 2000 (n=48). Trauma was the most frequent cause of admission, representing 54% (n=190), where 78% (n=148) corresponded to fractures. The information generated on the species entered into ex situ wildlife management sites is essential because there are considerable gaps in information for many species, especially for the Costa Rican Strigiformes.